Improving Junior High School Students' Mathematical Literacy Skills Through the Application of Problem Based Learning Models - Solfitri, Titi; Anggraini, Rini Dian; Rahma, Ati (FKIP - Universitas Riau, 2025)
The learning process in the classroom can be a trigger for low Mathematical Literacy Ability (KLM) of students so that improving the learning process and increasing students' KLM through the application of the Problem Based Learning (PBL) model is the purpose of this study. The research conducted was Classroom Action Research with two cycles on 35 students of class VIII-3 SMP Negeri 5 Pekanbaru. Data acquisition through learning device instruments (teaching modules equipped with teaching materials, LKPD, Remedial and Enrichment) and data collection instruments (observation sheets and student KLM test devices). The CAR cycle process was carried out in two cycles, covering four stages (planning, action, observation, and reflection) showing an increase in the average score of students' KLM from 54.46 in cycle I to 74.06 in cycle II. These results indicate that through the application of PBL, it can improve the learning process and increase the KLM of students VIII-3 SMP Negeri 5 Pekanbaru.